The Relationship Between the Provision of Complementary Feeding (MP-ASI) and Nutritional Status in Children Aged 6-24 Months at The Sikumana Health Center Kupang - Syahrir, Syahrir; Putri Bhwa, Daeng Agus Vieya; Ninef, Violin Irene; Romana Marawali, Fransiska; Adelia Tamelab, Chandika Jeklin (Jurnal Vocational Nursing Sciences (VNUS), 2024)
Introduction: The provision of Complementary Feeding (MP-ASI) for children is a critical stage in growth and development, especially between the ages of 6-24 months. During this period, children transition from exclusive breastfeeding to other foods that support their nutritional needs. Inadequate MP-ASI can lead to nutritional problems that affect children's health and development. This study aims to examine the relationship between the provision of MP-ASI and nutritional status in children aged 6-24 months at the Sikumana Health Center in Kupang. Objective: This study aims to evaluate the impact of MP-ASI on the nutritional status of children aged 6-24 months and to assess whether the type and timing of MP-ASI affect children's nutritional status. Method: This research used a descriptive analytic design with a cross-sectional approach. The study population consisted of children aged 6-24 months visiting the Sikumana Health Center. A total of 100 children were selected using simple random sampling. Data was collected through questionnaires, measurements of weight and height, and observations of MP-ASI practices. Descriptive statistics were used for data analysis, and the relationship between MP-ASI provision and nutritional status was analyzed using chi-square tests. Results: The majority of children (70%) who received adequate and timely MP-ASI had good nutritional status. Children who did not receive adequate or timely MP-ASI showed higher rates of malnutrition. Chi-square analysis showed a significant relationship between MP-ASI provision and nutritional status (p<0.05). Conclusion: The study concluded that appropriate MP-ASI provision is related to children's nutritional status. These findings are important for nursing practice, emphasizing the importance of educating about proper MP-ASI in primary healthcare settings.